2014
DOI: 10.2147/ndt.s72087
|View full text |Cite
|
Sign up to set email alerts
|

Can low brain-derived neurotrophic factor levels be a marker of the presence of depression in obese women?

Abstract: ObjectiveDepression is a common condition in obese women that can result in severe impairment of their physical and social functioning. A deficiency of brain-derived neurotrophic factor (BDNF) is involved in the mechanism of depression. The aim of this study is to investigate whether BDNF levels differ between obese female patients and healthy controls and whether BDNF levels alter with affective states in depressive obese women.MethodsThe study group included 40 obese, 40 preobese, and 40 normal weight women.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 49 publications
2
13
0
Order By: Relevance
“…However, while the two groups shown different level of serum concentration of BDNF, such a difference did not emerge about S100B. The prominent role of the neurotrophin BDNF in survival, growth, and maintenance of neurons during development 43,44 also in pathological conditions (see Habtemariam, 2018 73 for a recent review) is well established, while it still need to be completely clarified its role in obesity; indeed we registered higher level of BNDF in our sample of individuals affected by obesity, respect to healthy-weight controls, and this result is in line with previous studies in the field 74,75 ; however, it should be noted that reduced level of circulating BDNF levels in individuals affected by obesity respect to controls 76,77 as well as no differences between the two groups 78 were also reported. Nevertheless, there is an overall consensus in suggesting the possible critical role of BDNF in obesity; altered BDNF production was found to be associated with weight loss and food behavior in experimental animal models 7981 and in humans 82 .…”
Section: Discussionsupporting
confidence: 90%
“…However, while the two groups shown different level of serum concentration of BDNF, such a difference did not emerge about S100B. The prominent role of the neurotrophin BDNF in survival, growth, and maintenance of neurons during development 43,44 also in pathological conditions (see Habtemariam, 2018 73 for a recent review) is well established, while it still need to be completely clarified its role in obesity; indeed we registered higher level of BNDF in our sample of individuals affected by obesity, respect to healthy-weight controls, and this result is in line with previous studies in the field 74,75 ; however, it should be noted that reduced level of circulating BDNF levels in individuals affected by obesity respect to controls 76,77 as well as no differences between the two groups 78 were also reported. Nevertheless, there is an overall consensus in suggesting the possible critical role of BDNF in obesity; altered BDNF production was found to be associated with weight loss and food behavior in experimental animal models 7981 and in humans 82 .…”
Section: Discussionsupporting
confidence: 90%
“…It was found that the G196A polymorphism in the BDNF gene is associated with a higher probability of acute cerebrovascular incident [ 16 ]. Low concentrations of BDNF in the blood were observed in patients with risk factors for stroke, such as coronary artery disease, acute coronary syndrome, diabetes mellitus, metabolic syndrome, obesity, and physical inactivity [ 17 19 ]. In the present study, significantly lower levels of BDNF were observed in patients over 65 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a significant reduction of circulating BDNF levels in obese subjects versus controls was found [ 28 , 29 ], suggesting a negative association between circulating BDNF and this pathology [ 11 , 19 ]. However, in the last few years this relationship was called into question.…”
Section: Introductionmentioning
confidence: 99%